Determinants of willingness to pay for Hepatitis B vaccination in Malaysia - Rajamoorthy, Yogambigai (Universiti Putra Malaysia Press, 2017)
Hepatitis B infection is an upcoming health problem in Malaysia. HB vaccine coverage of infants in Malaysia was implemented by the Malaysian government in 1989. However, there is no compulsory vaccination programme for adults for HB vaccination. Currently, they have to protect themselves with a self-paid HB vaccination. The determinant of willingness to pay for HB vaccination is important to examine in order to estimate the economic benefit of high-burden diseases, such as HB. This study includes a few determinants identified by a literature review and an added new variable as risk behaviour to determine willingness to pay.